COVID-19 Lockdown containment measures and women’s sexual and reproductive health in Zimbabwe - Anniegrace M. Hlatywayo (AOSIS (Pty) Ltd., 2023)
The devastating COVID-19 pandemic and its accompanying containment measures brought exceptional challenges to the health delivery system, and in particular, women’s sexual and reproductive healthcare (hereafter referred to as SRH). The re-routing of health resources and funding to mitigate the effects of the pandemic obstructed the provision of essential SRH services for women and girls. Coupled with the incessant socio-cultural and patriarchal norms and gender inequalities, the COVID-19 pandemic aggravated the pre-existing SRH disproportions already affecting women. By adopting a qualitative approach and drawing on the experiences of women from three high density suburbs in Harare. Firstly, the study sought to explore the implications of the COVID-19 pandemic on SRH for women and girls. Secondly, the research sought to determine key drivers that affect women’s SRH in the context of COVID-19. Participant responses indicated that the COVID-19 lockdown containment measures which confined spouses to the home setting for prolonged periods of time, which is in contrast to the norm, exposed women to SRH related challenges. Participants cited that (i) bruised male ego due to lack of employment as a result of downscaling of companies resulting from COVID-19 containment measures resulted in men asserting their masculinities through heightened sexual intercourse, (ii) restraint of movement resulted in limited time for men to visit their small houses and side-chicks or side dish (euphemisms for illicit sexual relations) therefore resulting in frequent and unprotected sex with their spouses, giving rise to unplanned pregnancies and increased exposure to STIs due to limited access to SRH services and, (iii) increased intimate partner violence (IPV) and sexual abuse. Therefore, the research sought to explore the response of religious leaders and faith-based actors to providing psycho-social support and safe spaces as ways of addressing intersectional injustices giving rise to SRH challenges for women and girls.